EXPERIMENTAL STUDY OF THE PRESSURE DROP OF THE ECOFLUID R1234YF COMPARED TO THE FLUID R134A IN SMOOTH TUBES WITH 4.8MM INTERNAL DIAMMETER - Mendes, R. P.; Pottie, D. L.; Martins, L. V. S.; Pabon, J. J. G.; Machado, L. (Revista de Engenharia Térmica, 2020)
The refrigerant fluid R1234yf is a hydrofluorefine with zero potential for degradation of the ozone layer and low potential for global warming. It is one of the potential substitutes for the currently used R134a in automotive systems. In this work, the pressure drop suffered by the fluids R134a and R1234yf when flowing in a test section through a pipe with a 4.8 mm internal diameter was measured. The pressure drop was plotted as a function of the void fraction at the exit of the test section and the values were compared concerning the change in mass flux, change in saturation temperature, and comparatively between R1234yf and R134a. A significant increase in pressure drop was observed by the increases of the mass flux, showing an increment of 155.46% of the pressure loss from 200 to 300 kg·m-2·s-1 for R1234yf at 35ºC and 161.07% for R134a in the same conditions. Despite being high, those values are expected since increasing mass flux also increases the friction between both phases. On the other hand, by increasing the saturation temperature, the pressure drop is slightly lower once the differences between the densities of the liquid and vapor phases are reduced. Compared with R134a, the R1234yf ecofluid presents less pressure drop, showing a reduction of 24% for 300 kg·m-2·s-1.